Early stage cervical cancer: Brachytherapy followed by type a hysterectomy versus type B radical hysterectomy alone, a retrospective evaluation. Issue 3 (March 2016) - Lacorre, A.; Merlot, B.; Garabedian, C.; Narducci, F.; Chereau, E.; Resbeut, M.; Minsat, M.; Leblanc, E.; Houvenaeghel, G.; Lambaudie, E.
Abstract: Background: Two options are possible for the management of early stage cervical cancer, without lymph node involvement: radical surgery or brachytherapy followed by surgery. The aim of this study was to compare overall survival (OS) and disease-free survival (DFS) of early stage cervical cancers managed by uterovaginale brachytherapy followed by extrafasciale hysterectomy (group 1) or by radical hysterectomy alone (group 2). The secondary objectives were to compare the morbidity of these two different approaches and to evaluate the parametrial involvement rate in patients managed by radical hysterectomy. Materials and methods: It is a retrospective and collaborative study between the Paoli Calmettes Institute (Marseille) and the Oscar Lambret Center (Lille) from 2001 to 2013, in patients with tumors FIGO stages IA1, IA2, IB1 and IIA less than 2 cm of diameter, without pelvic lymph node involvement. Results: One hundred and fifty-one patients were included (74 in group 1 and 77 in group 2). The demographic characteristics of the two groups were comparable. OS and DFS were respectively 92.3% versus 100% (p = 0.046) and 92.3% and 98.7% (p = 0.18). Complication rates were 12.2% and 44.2%, respectively (p < 0.0001). In group 2, the parametrial invasion rate in this study was 1.30%. Conclusion: In our study, the two strategies are comparable in terms of DFS. Complications seem more frequent in the group 2, but more severe in the group 1. Finally, the low rate of parametrial invasion in group 2 confirms the interest of a less radical surgical treatment in these stages with good prognosis.